N4BP3 Regulates RIG-I-Like Receptor Antiviral Signaling Positively by Targeting Mitochondrial Antiviral Signaling Protein - Wang, Chen; Ling, Ting; Zhong, Ni; Xu, Liang-Guo (Frontiers in Microbiology, 2021)
Mitochondrial antiviral signaling protein (MAVS), an adaptor protein, is activated by RIG-I, which is critical for an effective innate immune response to infection by various RNA viruses. After infection, the Rig-like receptor (RLR) recognizes pathogen-derived dsRNA and then becomes activated to promote prion-like aggregation and activation of MAVS. Subsequently, through recruitment of TRAF proteins, MAVS activates two signaling pathways mediated by TBK1-IRF3 and IKK- NF-κB respectively and turns on type I interferon and proinflammatory cytokines. In this study, we discovered that NEDD4 binding protein 3 (N4BP3) is involved in the RLR signaling pathway as a positive regulator by targeting MAVS. Overexpression of N4BP3 promoted virus-induce the interferon-β (IFN-β) promoter and interferon-stimulated response element (ISRE). Further experiments showed that knockdown or knockout N4BP3 distinctly inhibited RIG-I-like receptor (RLR)-mediated innate immune response. We also detected that N4BP3 can accelerate the interaction between MAVS and TRAF2. Related experiments also revealed that N4BP3 can facilitate the ubiquitination modification of MAVS. In conclusion, the experimental results indicate that N4BP3 acts as a positive regulator of virus-induced RLR signaling pathway by targeting MAVS, which also provides insight into the mechanisms of innate antiviral responses.